The Lorentz structure of semi-hadronic tau decays - Dova, María Teresa (1996)
Semi‐hadronic tau decays provide a powerful tool to study the Lorentz structure of the weak charged current. Using decays of the τ into a1 it is possible to extract tau polarization Pτ and tau neutrino helicity γVA. A method is presented to determine the tau neutrino helicity independent of any tau polarization which may be present.